GAYA KEPEMIMPINAN REKTOR INSTITUT AGAMA ISLAM SULTAN MUHAMMAD SYAFIUDDIN SAMBAS PERIODE 2006-2020 - Budiman Budiman (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2022)
The progress and withdrawal of an institution depends on the leadership of its leadership, including the private university in Sambas, namely the Sultan Muhammad Syafiuddin Sambas Islamic Religious Institute. It seems that the progress achieved by the IAIS Rector, Sambas, as the leader in carrying out the construction of higher education institutions at IAIS Sambas from 2006 to 2020.This research uses mixed methods, which combines qualitative research with quantitative research. The data techniques used in this research are observation, interview and documentation, survey, and FGD. Meanwhile, to check the validity of the data using triangulation data validity techniques, data validity checking techniques that make use of something outside the data for checking purposes or as a comparison. While data analysis in this study used data analysis based on qualitative and quantitative data analysis, namely data that had been collected and declared complete, the researcher conducted qualitative data analysis by describing data from interviews, observations, documentation, surveys and FGDs and then pulled them out conclusion. The results showed that; 1. Broadly speaking, Dr. H. Jamiat Akadol, M.Sc., MH as the Rector of IAIS Sambas in managing higher education institutions has implemented the four leadership styles according to Robbins, namely the charismatic style, transactional style, transformational style and visionary style. 2. Dr. leadership style H. Jamiat Akadol, M.Sc., MH as the Rector of IAIS Sambas which is more dominant is the Charismatic leadership style which is supported by the results of qualitative analysis and coupled with the results of the FGD. The progress and withdrawal of an institution depends on the leadership of its leadership, including the private university in Sambas, namely the Sultan Muhammad Syafiuddin Sambas Islamic Religious Institute. It seems that the progress achieved by the IAIS Rector, Sambas, as the leader in carrying out the construction of higher education institutions at IAIS Sambas from 2006 to 2020.This research uses mixed methods, which combines qualitative research with quantitative research. The data techniques used in this research are observation, interview and documentation, survey, and FGD. Meanwhile, to check the validity of the data using triangulation data validity techniques, data validity checking techniques that make use of something outside the data for checking purposes or as a comparison. While data analysis in this study used data analysis based on qualitative and quantitative data analysis, namely data that had been collected and declared complete, the researcher conducted qualitative data analysis by describing data from interviews, observations, documentation, surveys and FGDs and then pulled them out conclusion. The results showed that; 1. Broadly speaking, Dr. H. Jamiat Akadol, M.Sc., MH as the Rector of IAIS Sambas in managing higher education institutions has implemented the four leadership styles according to Robbins, namely the charismatic style, transactional style, transformational style and visionary style. 2. Dr. leadership style H. Jamiat Akadol, M.Sc., MH as the Rector of IAIS Sambas which is more dominant is the Charismatic leadership style which is supported by the results of qualitative analysis and coupled with the results of the FGD.